Retinoic acid as a novel medical therapy for Cushing's disease in dogs - Castillo, V. (2006)
Cushing's disease is almost always caused by an ACTH-secreting pituitary tumor, but effective medical therapy is currently limited. Because retinoic acid has been shown to be potentially useful in decreasing corticotroph secretion and proliferation in rodent models, we have studied its action in dogs with Cushing's disease. A randomized treatment with retinoic acid (n = 22) vs. ketoconazole (n = 20) in dogs with Cushing's disease was assigned for a period of 180 d. Clinical signs, plasma ACTH and α-MSH, the cortisol/creatinine urine ratio, and pituitary magnetic resonance imaging were assessed and compared at different time points. We recorded a significant reduction in plasma ACTH and α-MSH, and also in the cortisol/ creatinine urine ratio, of the dogs treated with retinoic acid. Pituitary adenoma size was also significantly reduced at the end of retinoic acid treatment. Survival time and all the clinical signs evaluated showed an improvement in the retinoic-acid-treated dogs. No adverse events or signs of hepatotoxicity were observed, suggesting that the drug is not only effective but also safe. Retinoic acid treatment controls ACTH and cortisol hyperactivity and tumor size in dogs with ACTH-secreting tumors, leading to resolution of the clinical phenotype. This study highlights the possibility of using retinoic acid as a novel therapy in the treatment of ACTH-secreting tumors in humans with Cushing's disease. Copyright © 2006 by The Endocrine Society.